(untitled) (Acta Scientiarum. Animal Sciences, 2018)
This study evaluated the pH and contents of dry matter (DM) and lactic acid (AL) of sugarcane silages added with different levels of inclusion of macaúba cake (TM) in different opening times (TA), in days. Laboratory silos used were opened at times 0; 3; 7; 12; 24; 36; 41 and 60 days after ensiling. The response surface methodology was used for statistical analysis. The DM content was influenced by both NI and TA. The inclusion of TM contributed to increase the DM content of sugarcane, as it absorbed moisture of the ensiled sugarcane. The pH values were influenced only by TA, which were lower than 3.8. The AL content was influenced by both NI and TA, that is, the inclusion of TM favored the increase of AL content over the 60 days evaluated. It can be concluded that the inclusion of TM in sugarcane silage can be used in all NI evaluated, and the silages should be stored for 60 days to ensure the adequate fermentation process inside the silos.